REVIEW AND ANALYSIS OF PREVIOUS RESEARCHES IN THE SPHERE OF ENSURING THE PROTECTION OF INFORMATION AND EDUCATIONAL ENVIRONMENT OF UNIVERSITIES - L. Kydyralina; B. Akhmetov; V. Lakhno; A. Adranova (Scientific Journal of Pedagogy and Economics, 2019)
The paper reviewed and analyzed previous researches in the field of protection of the information and educational environment of universities (IEEU). It is shown that the priority development of digital education systems in many industrialized countries of the world requires appropriate technical and methodological support of specialists not only in the field of pedagogical activity, but also in information technology, taking into account the problems of cyber security and information protection. It is shown that the protected data that is stored and circulate in the information and communication systems of universities, in particular, include: personal data of students, teachers, researchers, support staff; digitized information representing the intellectual property of an educational institution; information arrays that provide educational process (for example, multimedia content, databases, tutorials); others. It is substantiated that these information resources can act as an object of theft or distortion from external (internal) computer intruders or from hooligan motives, from the side of students or employees. It is substantiated that the trend towards globalization of access to information resources, formed in many countries, makes relevant the task of implementation the latest digital and information and communication technologies in all areas of activity of a modern university. The relevance of research in the direction of development of the models for decision support systems for finding investment control strategies for various ratios of the parameters of the investment process in the cyber security systems of educational institutions is also proved. There is shown the necessity of computer support for solving problems of finding investment control strategies in the cyber security strategies of educational institutions. There is described the necessity of developing a conceptual model of the adaptive control of cyber security of an informatization object on the example of IEEU.